Effect of Open and Closed Endothracheal Suctioning on Physiologic Parameters and Stability in Premature Infants undergoing Mechanical Ventilation - Leila Valizadeh; Rahele Janani; Alehe Seyedrasooli; Abdollah Janat Dust; Mohammad Asghari Jafarabadi (Tehran University of Medical Sciences, 2014)
Background & Aim: Premature infants are the most admitted group to NICUs. Stabilization of cardio pulmonary parameters is a main goal in NICUs. Mechanical ventilation and endothracheal suctioning are the most common and effective procedures to stabilize cardio pulmonary parameters. The aim of present study was to compare the effects of two endothracheal suctioning methods (open and closed) on physiological stability in premature infants under mechanical ventilation .   Methods & Materials: In this clinical trial, 90 preterm infants (GA: 27-34 weeks) hospitalized in the NICUs of Alzahra and Taleghani hospitals were selected and randomly assigned to two groups. In one group, infants were suctioned using open suctioning method and in the other group, infants were suctioned using closed suctioning method. The physiologic parameters (O2 sat, HR, mean BP variation) and stability (recovery time of HR, BP) were compared between the groups. Data were analyzed using descriptive and inferential statistical methods such as x2, independent t-test and mixed model in the SPSS-21 .   Results: There was significant statistical difference between the two groups on mean BP (P=0.016). Recovery time of the BP and HR was shorter in the closed suctioning group. Physiologic stability was better in the closed suctioning group (P<0.05) .   Conclusion: Variation of the mean BP and recovery time was more in the open suctioning group compared with the closed suctioning group. Considering better physiologic effects of closed suctioning, it is recommended to assess the combined effect of closed suctioning with weight on physiologic parameters of premature infants .